Mosaic trisomy 21 at amniocentesis in a twin pregnancy associated with a favorable fetal outcome, maternal uniparental disomy 21 and postnatal decrease of the trisomy 21 cell line - Chih-Ping Chen; Te-Yao Hsu; Schu-Rern Chern; Peih-Shan Wu; Shin-Wen Chen; Liang-Kai Wang; Fang-Tzu Wu; Yen-Ting Pan; Chen-Chi Lee; Yun-Yi Chen; Wayseen Wang (Elsevier, 2023)
Objective: We present mosaic trisomy 21 at amniocentesis in a twin pregnancy associated with a favorable fetal outcome, maternal uniparental disomy (UPD) 21 and postnatal decrease of the trisomy 21 cell line. Case report: A 36-year-old woman underwent elective amniocentesis at 16 weeks of gestation because of advanced maternal age, and an abnormal non-invasive prenatal testing (NIPT) result suggesting trisomy 21. Amniocentesis revealed the karyotype of 46, XX in co-twin A and the karyotype of 47,XY,+21[12]/46,XY[21] in co-twin B in the cultured amniocytes by in situ culture method. Simultaneous array comparative genomic hybridization (aCGH) analysis on uncultured amniocytes revealed the result of arr (21) × 3 [0.40] in co-twin B, consistent with 40% mosaicism for trisomy 21. Prenatal ultrasound was unremarkable, and the parental karyotypes were normal. Following genetic counseling, the parents decided to continue the pregnancy. At 36 weeks of gestation, a 2140-g female co-twin A and a 1800-g male co-twin B were delivered without any phenotypical abnormality. The karyotypes of the umbilical cord and placenta of co-twin B were 47,XY,+21[16]/46,XY[24] and 47,XY,+21 (40/40 cells), respectively. Quantitative fluorescence polymerase chain reaction (QF-PCR) analysis on the DNA extracted from parental bloods and umbilical cord, cord blood and placenta and peripheral blood at age five months of co-twin B confirmed a maternal origin of trisomy 21 and maternal uniparental isodisomy 21. aCGH analysis on the cord blood revealed the result of arr 21q11.2q22.3 × 2.25 consistent with 20%-25% (log2 ratio = 0.15-0.2) mosaicism for trisomy 21. When follow-up at age five months, the co-twin B was phenotypically normal. His peripheral blood had a karyotype of 47,XY,+21[3]/46,XY[37]. Interphase fluorescence in situ hybridization (FISH) on 100 buccal mucosal cells detected no trisomy 21 signals. The peripheral blood had uniparental isodisomy 21. Conclusion: Mosaic trisomy 21 at amniocentesis can be a transient and benign condition and should alert the possibility of UPD 21. The abnormal trisomy 21 cell line in mosaic trisomy 21 at amniocentesis may decrease and disappear after birth.